Advantage of Trans Radial Coronary Angiography: A Study of 40 Patients - Patwary, Mohammad Saifullah; Uddin, Mir Jamal; Rahman, Md Mukhlesur; Haque, Syed Azizul; Ahmed, Md Khurshed; Haider, Sazzad; Fatema, Nilufar (University Heart Journal, 2010)
Percutaneous coronary catheterization and revascularization are commonly performed all over the world. Among various access sites for coronary interventions, most cardiologists favour the femoral approach, while the procedure via the radial artery is only performed by a limited number of operators. In this study, we aimed to assess the procedural outcome of the trans-radial coronary angiography (CAG) among the patients in a tertiary care hospital in Bangladesh. This prospective observational study was carried out among 40 patients underwent trans-radial coronary angiography. The study was conducted for a period of one year. Indication of CAG including chronic stable angina, unstable angina, non ST elevated myocardial infarction (MI) and ST elevated MI were observed. Procedural attempt, success rate and outcome with or without complications were mentioned. Out of 40 patients, 70% were male and 30% were female (M: F=2.3:1). Among the patients undergoing trans-radial CAG, 50% had dyslipidemia and HTN, 55% had family history of IHD, 52.5% were smoker and 20% had DM. Most of the patients underwent trans-radial CAG due to unstable angina (52.5%) and this was followed by ST elevated MI (30%), non ST elevated MI (10%) and chronic stable angina (7.5%).The mean procedural time was 19.85±1.3 minutes. The fluoroscopy time was 9.60±.9 minutes. The mean hemostasis time was 9.00±7.0 minutes. All patients were ready for discharge within 24 hours. Only 7.5% patients experienced spasm of radial artery during CAG. No other complications were detected. Trans-radial approach is an attractive alternative to conventional trans-femoral approach, in suitable patients at the hand of experienced operator, with appropriate hardwire and should be ready to cross over, to the femoral approach when needed. Keywords: Trans-radial coronary angiography; trans-femoral approach. DOI: 10.3329/uhj.v5i2.4553 University Heart Journal Vol.5(2) July 2009 pp.52-55